Apoptosis Exerts a Vital Role in the Treatment of Colitis-Associated Cancer by Herbal Medicine - Tian, Ruimin; Liu, Xianfeng; Luo, Yanqin; Jiang, Shengnan; Liu, Hong; You, Fengming; Zheng, Chuan; Wu, Jiasi (Frontiers in Pharmacology, 2020)
Colitis-associated cancer (CAC) is known as inflammatory bowel disease (IBD)-developed colorectal cancer, the pathogenesis of which involves the occurrence of apoptosis. Western drugs clinically applied to CAC are often single-targeted and exert many adverse reactions after long-term duration, so it is urgent to develop new drugs for the treatment of CAC. Herbal medicines commonly have multiple components with multiple targets and most of them are toxicity-low. At present, some herbal medicines have been reported to ameliorate CAC through inducing apoptosis, while there is still a lack of systematic review. In this work, we reviewed articles published in Sci Finder, Web of Science, PubMed, Google Scholar, CNKI and other databases in recent years by setting keywords as apoptosis in combination of colitis associated cancer. We summarized the herbal medicine extracts or their compounds that can prevent CAC by modulating apoptosis and analyzed the mechanism of action. The results show that: (1) Herbal medicines regulate both mitochondrial apoptosis pathway and death receptor apoptosis pathway. (2) Herbal medicines modulate the above two apoptotic pathways by affecting signal transductions of IL-6/STAT3, MAPK/NF-κ B, Oxidative stress, Non-canonical TGF-β1, WNT/β-catenin and Cell cycle, thereby ameliorating CAC. We conclude: (1) Studies on the role of herbal medicine in regulating apoptosis through Ras/Raf/ERK, WNT/β-catenin and Cell cycle pathway are not yet in-depth. (2) The active constitutes of reported anti-CAC herbal medicine mainly include polyphenols, terpenoids and saccharide. Also, we collected other herbal medicines with those constitutes mentioned above as main contents, aiming to provide a reference for the clinical use of herbal medicine in the treatment of CAC. (3) New dosage forms can be utilized to elevate the targeting and reduce the toxicity of herbal medicine.